Enhanced structural, electrical, mechanical properties and antibacterial activity of Cs/PEO doped mixed nanoparticles (Ag/TiO2) for food packaging applications - M.M. Abutalib (Elsevier, 2021)
In this paper, silver (Ag) nanoparticles were synthesized by utilizing an aqueous extract of fresh leaves of Chenopodium murale which is considered a cost-effective and eco-friendly approach. The sol-gel technique was used to syntheses TiO2 nanoparticles and different methods were used to characterize the nanoparticles (Ag and TiO2) including UV–Vis spectroscopy, XRD, and TEM. Also, new nanocomposites were prepared using the solution casting method. The prepared films were characterized by different analytical methods. The absorption peak of the silver nanoparticles shown by the UV–visible spectrum was around 430 nm. The crystalline average size of the Ag NPs was 20 nm while TiO2 NPs was 15 nm as displayed by the XRD pattern. Meanwhile, the degree of amorphicity of the Cs/PEO blend was increased as a result of adding Ag and TiO2 NPs. It was evident through the FTIR spectroscopy that there was an interaction between the functional groups of the polymer blend and the Ag/TiO2 nanofiller. In addition, there was an increase of mechanical properties of the prepared films such as the Young's modulus, elongation, and tensile strength with increasing the Ag/TiO2 content. It was clear through the impedance spectroscopic study that the iconic conductivity was improved with the addition of Ag and TiO2 nanoparticles into the polymer blend system. The highest conductivity was log −9.34 S cm−1 at Cs/PEO/0.3%Ag/0.8%TiO2. It was also evident from the results that the antibacterial activity of the pure Cs/PEO blend was increased as a result of doping Ag/TiO2 nanoparticles to the polymer blend. The activity index (%) of the antibacterial activity at sample blend + (0.3%) Ag + (0.8%) TiO2 of the E. coli, S. aureus, C. Albicans, A. niger was 32, 45.8, 77.8, and 92 (%) respectively. Thus, these results indicate the applicability and potential of the nanocomposites for use in food packaging applications.